Prescription opioid behaviors among adults with and without disabilities – United States, 2015–2016. Issue 3 (July 2019) - Lauer, Eric A.; Henly, Megan; Brucker, Debra L.
Abstract: Background: Prescription opioid use among people with disabilities has not been well characterized. Objective: To examine prescription opioid use, misuse, and use disorder, reason and source for last prescription opioid misuse, and receipt of prescription opioid treatment among people with and without disabilities. Method: Stratified analysis of prescription opioid use, misuse, and use disorders; primary reason and primary source for last prescription opioid misuse; receipt of prescription opioid treatment; and disability status among civilian, noninstitutionalized adults (ages 18+) using data from the 2015–2016 National Survey on Drug Use and Health. Results: Adults with disabilities were significantly more likely than adults without disabilities to experience past year prescription opioid use (52.3% for those with disabilities compared to 32.8% of those without), misuse (4.4% compared to 3.4%), and use disorders (1.5% compared to 0.5%). People with disabilities were significantly more likely to misuse opioids for pain (Risk Ratio = 1.5, p < 0.001) and to receive opioids from a healthcare provider (Risk Ratio = 2.0, p < 0.001). Among people with opioid use disorder, people with disabilities were less likely to receive treatment for prescription opioid use (Risk Ratio = 0.6, p = 0.067). Conclusion: In the U.S., a substantial population with disabilities using and misusing prescription opioids exists that has not been well characterized. Persons with disabilities experience disparities in reason and source for last opioid misuse. Healthcare and substance abuse prevention, intervention and treatment providers must collaborate to address the needs of this population.